Curriculum 2013 Implementation Workshop Curriculum 2013 In Learning In The District of Babar Islands – Southwestern Maluccas Regions - Mieke Souisa; Jacob Anaktototy; Wilhelmina Unmehopa; Mariana Hukubun; Emma Rumahlewang; Jonas Solissa; Johana Matitaputty (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
The 2013 curriculum has been approved and implemented in the Indonesian learning system, since a few years ago, to have undergone a number of improvements. Based on some studies in the cities of Ambon and Maluku particularly in the physical and exercise programs, indicates that a teacher's lack of ability to plan the learning process using the 2013 curriculum, both at an elementary level, middle school, and high school. Much of what follows, two are unfamiliar with the 2013 curriculum procedure in learning because it rarely participates in any related training. Subsequent methods used by teams for established purposes were achieved: (a) problem identification, (b) social approach, (c) discourse, (d) discussion, (e) evaluation, (f) drawing conclusions. Results based on the procedural process developed by understanding participants' concepts of curriculum 2013 implementation procedures, in both cases; (a) plan learning, (b) procedures in selecting and using and applying active learning models in saintifical, authentic and also thematic approaches in classroom learning, (c) the evaluation process in classroom learning, in order to create interactive students.